1997
DOI: 10.1002/(sici)1098-1136(199709)21:1<106::aid-glia12>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Use of fluorocitrate and fluoroacetate in the study of brain metabolism

Abstract: Fluoroacetate and its toxic metabolite fluorocitrate cause inhibition of aconitase. In brain tissue, both substances are preferentially taken up by glial cells and leads to inhibition of the glial TCA cycle. It is important to realise, however, that the glia-specificity of these compounds depends both on the dosage and on the model used. The glia-inhibitory effect of fluorocitrate as obtained by intracerebral microinjection in vivo is reversible within 24 h. A substantial inhibition of the glial TCA cycle by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 17 publications
3
94
0
1
Order By: Relevance
“…The needle track was the only confirmation of the injection site. Third, the dose of FC used will result in a decrease in glutamine, which is an important precursor for γ-aminobutyric acid (GABA) and glutamate (Fonnum et al, 1997). This will alter the release of these neuro-transmitters and may alter neuronal function (Paulsen et al, 1987;Keyser & Pellmar, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The needle track was the only confirmation of the injection site. Third, the dose of FC used will result in a decrease in glutamine, which is an important precursor for γ-aminobutyric acid (GABA) and glutamate (Fonnum et al, 1997). This will alter the release of these neuro-transmitters and may alter neuronal function (Paulsen et al, 1987;Keyser & Pellmar, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…FC is selectively taken up by glial cells and is a 'suicide' substrate for the enzyme aconitase. Therefore, it temporarily depresses glial function (Hassel et al, 1992;Berg-Johnsen et al, 1993;Swanson & Graham, 1994;Fonnum et al, 1997). The FC solution was prepared from its barium salt after precipitation of the barium with sodium sulphate, as described by Paulsen et al (1987).…”
Section: α-Aa and Fc Treatmentmentioning
confidence: 99%
“…Intriguingly, electrophysiological analyses have shown that the spontaneous activity of GnRH neurons in these animals is decreased and that this deficiency is mimicked by the bath application of either fluoroacetate, an inhibitor of astrocyte metabolism (Fonnum et al, 1997; Henneberger et al, 2010), or the COX blocker indomethacin, to slices of the preoptic region from wild-type animals (Clasadonte et al, 2011). The fact that GnRH neuronal activity in all these conditions can be rescued by exogenous PGE 2 (Clasadonte et al, 2011) strongly suggests that glial PGE 2 is an important component of the homeostatic mechanism controlling GnRH neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…These results formed the basis of the assumption that glia plays the most important role in the stimulation-induced signal change. In view of the pleomorphic effects furosemide exerts at such high concentrations used in the above experiments (Gutschmidt et al, 1999), we have chosen a different approach by employing antidromic stimulation and application of FAC as a tool to selectively block glial cells (Fonnum et al, 1997). The substance significantly decreased slope and the maximum amplitude of the intrinsic optical signal, without affecting most electrophysiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that the substance in concentrations used exerts non-specific and pleomorphic effects, including reduced neuronal excitability, interference with glial volume regulation mechanisms and pronounced changes in extracellular pH (Gutschmidt et al, 1999). In the current experiments we have tried to circumvent some of those methodological limitations by selectively blocking glial function with fluoroacetate (FAC) (Fonnum et al, 1997). Finally, on a subcellular level changes in size of mitochondria also appear to contribute to the generation of the intrinsic optical signal change during neuronal activation.…”
Section: Introductionmentioning
confidence: 99%